THE INFLUENCE OF GUIDED DISCOVERY LEARNING MODEL TOWARD CRITICAL THINKING SKILLS OF X GRADE STUDENTS AT SMA NEGERI KARANGPANDAN IN ACADEMIC YEAR 2013/2014. - -, Fuad Haris, Yudi Rinanto, Umi Fatmawati (P Biologi FKIP UNS Surakarta, 2015)
- The purpose of this research is to know the influence of Guided Discovery Learning toward critical thinking skills of X grade students at SMA Negeri Karangpandan in academic year 2013/2014. The research was a quasi-experimental. The research design was used post-test only nonequivalent control group design with the experiment group applying model and control group applying conventional learning model. The population of this research was all of X grade students at SMA Negeri Karangpandan in academic year 2013/2014. Sampling techniques used cluster sampling that choosed X 1 grade as control group and X 2 grade as experiment group. Techniques of collecting data were test and non-test methods. The test method examinate critical thinking test. The non-test method included observation of activities student and documentation. The hypothesis was analyzed by t-test. This research concluded that the Guided Discovery Learning model affected (Sig.0,000<0,05) the critical thinking skills of X grade students at SMA Negeri Karangpandan in academic years 2013/2014.Keywords : Guided Discovery Learning, Critical Thinking Skills.